Das Internet in Deutschland: Regionale Strukturen und Wachstumsmuster — das Beispiel der „.de-Domains” - Langhagen-Rohrbach, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
The Internet as a virtual medium is often considered to be placeless. This article tries to find out that even the Internet has a regional structure in “real” space. This structure depends on infrastructure (networks) as well as on existing spatial patterns of places. So the Internet intensifies existing regional disparities. The growth pattern of the Internet in Germany shows the same pattern as it is well known from the diffusion of any other innovation. The German Internet Toplevel-Domain “.de” is an example of this growth pattern in Germany.